Web-based information system for submission of standard operational procedures - Surahman Surahman; Purwono Hendradi; Agus Setiawan (Universitas Muhammadiyah Magelang, 2021)
Internal quality assurance system in Muhammadiyah university of Magelang has been applied since 2009. One of the quality assurance systems is the Standard Operating Procedure (SOP) in working-units. SOP is related to step-by-step instruction of operation, where the operation is conducted, what the operation is, how to do it, when to do it, and who are involved in the operation. Therefore, each activity in working-unit, either internal or external, must follow the applicable SOP. The current SOP proposal is in form of printed hardcopy. It is considered less effective. In addition, hardcopy extends the review process. Moreover, the validated SOP could not be identified well. This study builds web-based standard operating procedure (SOP) proposal information system aiming at solving those problems. The system can be used by all working-units in Muhamamdiyah University of Magelang. This system manages all validated SOP by the authority. It also reports the number of SOP for each standard, number of SOP in each working-unit, and the whole SOP in the university.